If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2y+5=(3y-3)
We move all terms to the left:
-2y+5-((3y-3))=0
We calculate terms in parentheses: -((3y-3)), so:We get rid of parentheses
(3y-3)
We get rid of parentheses
3y-3
Back to the equation:
-(3y-3)
-2y-3y+3+5=0
We add all the numbers together, and all the variables
-5y+8=0
We move all terms containing y to the left, all other terms to the right
-5y=-8
y=-8/-5
y=1+3/5
| 2/15=3/2(4/9x+3) | | 2n+7=7n-3 | | -10g=9–7g | | 2/3x+14=1/3x+12 | | 5x-3(4-2x)+6=0 | | 0.8aa=7.5 | | 2/3x+1/11=-1/3x-1/3 | | k−8=11.8 | | 2c-8=c+14 | | 0.2x+3=0.27x+2.7 | | 8(3x+4)-5(6x)=20 | | -8+3r=3r-7 | | 9(c-8)+5=-67 | | −4.3g=25.8 | | −7.5(x−3)=3.75 | | 2/3=6/v | | x;3x-5=1/2x+2x= | | -9a+4=a+204 | | 5x/3x+5=2 | | -5a-8a=0 | | 8p-5=5p+7 | | 4(x-2)=(x+2) | | 9x+75=10x-20 | | 2(4x-4)+4x+5=-111 | | Y=3x^2+22x+24 | | 3k+6(7-5k)=231 | | 6x2+30x+36=0 | | (5n-4)(n-7)=0 | | 7(4x+3)=273 | | c-59=5c+9 | | x/3x-5=1/2x+2x | | x/9+2/3=4/9 |